Overexpression of soybean GmNAC19 and GmGRAB1 enhances root growth and water-deficit stress tolerance in soybean - Mazarei, Mitra; Routray, Pratyush; Piya, Sarbottam; Stewart, C. Neal; Hewezi, Tarek (Frontiers in Plant Science, 2023)
Soybean (Glycine max) is an important crop in agricultural production where water shortage limits yields in soybean. Root system play important roles in water-limited environments, but the underlying mechanisms are largely unknown. In this study, a transcriptome analysis of RNA-seq data generated from roots of soybean at three different growth stages (20-, 30-, and 44-day-old) was performed to select candidate genes with probable association with root growth and development. Candidate genes were functionally examined in soybean by overexpression of individual genes using intact soybean composite plants with transgenic hairy roots. Root growth and biomass in the transgenic composite plants were significantly increased by overexpression of the GmNAC19 and GmGRAB1 transcriptional factors, showing up to 1.8-fold increase in root length and/or 1.7-fold increase in root fresh/dry weight. Furthermore, greenhouse-grown transgenic composite plants had significantly higher seed yield for about 2-fold than control plants. Expression profiling in different developmental stages and tissues showed that GmNAC19 and GmGRAB1 were most highly expressed in roots, displaying a distinct root-preferential expression. Moreover, we found that under dehydration conditions, overexpression of GmNAC19 enhanced water stress tolerance in transgenic composite plants. Taken together, these results provide further insights into the agricultural potential of these genes for development of soybean cultivars with improved root growth and enhanced tolerance to dehydration conditions.